(untitled) (The Journal of Plant Protection Sciences, 2020)
A field experiment was conducted during winter season of 2004-05 and 2005-06 to evaluate the effectiveness of different conventional & eco-friendly insecticide (synthetic and biological origin) against thrips (Scirtothrips dorsalis Hood) infesting chilli (Capsicum frutescens). The effectiveness of four insecticides acetamiprid 0.004% (Dhanpreet – 20% SP), thiamethoxam 0.005% (Avant-25% WG), neem pesticide 0.4% (ultineem 1% W/W) and Bacillusthuringiensis, subsp. kurstaki (BT) at gL- 1 was evaluated in the field of Coastal Saline Zone of West Bengal against thrips. It is evident from the result of present investigation that acetamiprid and thiamithoxam were mo BT (43.43%) were found moderately effective. However, two sprays of acetamiprid and thiamethoxam followed by two sprays of neem pesticide and BT proved to be effective for management of thrips and it gave highest marketable yield, higher cost benefit ratio and percent reduction in thrips’ population.